Transoral surgery in t1-t2 staged laryngeal cancer - Ruggeri, Carlos Santiago; Latourrette, Dora Cristina; Legris, Ana; Acosta, Lautaro; Bedini, Ivo (Revista del Hospital Italiano de Buenos Aires, 2020)
A prospective and descriptive study was conducted, including 103 patients who were treated for early stage laryngeal cancer (T1-T2) with transoral surgery. Of these, 55 were diagnosed in stage T1, 16 in stage T1-b and 32 in stage T2. The initial local control (CLI) in patients with malignant T1 laryngeal tumors was: 91%, local control with rescue (CLR) 96%, preservation of larynx function (PFL) 93% and specific survival 96%. In T1-b the CLI was 81%, the CLR 94%, the PFL 94% and the specific survival 94%. In T2 the CLI was 63%, the CLR 94%, the PFL 72% and the specific survival 78%. Transoral surgery in laryngeal cancer with initial T has oncological results similar to other treatments (external surgery or radiotherapy), but we consider that it is the best option because of its low morbidity, shorter duration of treatment, and because it leaves open all the possibilities to treat possible recurrences.
Keywords: larynx cancer; transoral surgery; T1; T2